Taxation, Wage Variation, and Job Choice - Brown, James N.; Rosen, Harvey S. (Journal of Labor Economics, 1987)
This paper examines the effect of earnings taxes on wage variability over time. We estimate a "hedonic wage locus," which indicates how the market allows individuals to substitute the mean level of the wage for its variability across jobs. Information from this locus is used to estimate the parameters of individuals' indifference curves between the mean and temporal variation of hourly wages. On the basis of these utility-function parameters, we predict that lowering the rate of taxation on earnings would on average lead workers to choose jobs with slightly lower pretax mean wages and with less pretax wage variation.